Influence of the pedicle orientation and length on viability of unipedicled venous island flaps. Issue 3 (27th August 2013) - Han, Seung‐Kyu; Kim, Soo‐Young; Gu, Ja Hea; Jeong, Seong‐Ho; Kim, Woo‐Kyung
<x xml:space="preserve">Abstract</x> The use of unipedicled venous flaps has been limited due to their unconventional perfusion patterns and inconsistent survival. Further information regarding the optimal conditions required for unipedicled venous flap coverage is needed to increase flap survival. The purpose of this study was to investigate the effect of the pedicle orientation and length on the viability of unipedicled venous flaps based on a review of our clinical experience. Thirty‐one skin and soft tissue hand defects of 29 patients were treated with unipedicled venous flaps. Sixteen defects were treated with proximally pedicled flaps and 15 were treated with distally pedicled flaps. Five of the 16 proximally pedicled flaps and eight of the 15 distally pedicled flaps had pedicle lengths ≥ 5 cm. All proximally pedicled flaps survived, and distally pedicled flaps with pedicle lengths <5 cm (n = 7) also survived. Distally pedicled flaps with pedicle lengths ≥5 cm (n = 8) developed congestion within 1–2 days after surgery, and external bleeding was applied. Four of the eight flaps survived completely, and partial necrosis developed in the other four. The results demonstrate that proximally pedicled venous flaps of the hand can survive regardless of pedicle length. Distally pedicled venous flaps can also survive completely when pedicle length is <5 cm. Distally pedicled venous flaps with pedicle lengths ≥5 cm should be used with caution. © 2013 Wiley Periodicals, Inc. Microsurgery 34:197–202, 2014.